1981
DOI: 10.1104/pp.68.2.382
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Membrane Fluidity during Development of Freezing Tolerance of Winter Wheat Seedlings

Abstract: Fluidity of membrane lipids of shoot and root tissue and of chloroplasts from young wheat seedlings of contrasting freezing tolerance was investigated by measuring the motion and order parameters after spin labeling. A striking similarity was observed in membrane lipid fluidity of the five cultivars grown at 22 C. After cold hardening by growth at 2 C, a small change in membrane lipid fluidity was observed, but this was not correlated with the development of freezing tolerance, and there was no alteration in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 14 publications
1
5
1
Order By: Relevance
“…While some workers have, suggested a correlation between membrane increased permeability and/or fluidity, and freezing tolerance (7,16), others have fo -id no correlation (11). In this study, increased Kp (e.g.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While some workers have, suggested a correlation between membrane increased permeability and/or fluidity, and freezing tolerance (7,16), others have fo -id no correlation (11). In this study, increased Kp (e.g.…”
Section: Discussioncontrasting
confidence: 55%
“…Changes in membrane characteristics upon acclimation to low temperature have been studied and attempts have been made to correlate these with changes in freezing tolerance. Most of these studies have focused on changes in the composition and fluidity of the lipid portion of cellular membranes upon acclimation (4,11,12,16,17). Changes in membrane lipid and fatty acid composition could be involved in maintaining membrane fluidity, stability, and function at low temperatures (5,10,17).…”
mentioning
confidence: 99%
“…Although this concept has been accepted widely, recently it has been questioned in view of the apparent similarity in whole root membrane fluidity and the transition temperature of membrane lipids demonstrated with several wheat cultivars grown at 2 and 22°C (17). Other reports (3,6,9,16) also have suggested that changes in fatty acid composition of membranes are not required for cold acclimation of a number of plant species.…”
mentioning
confidence: 99%
“…The DBI values of lipids from old and new roots increased with time at all temperatures (Table III). In old roots, DBI values were not different among tempera- (3,6,9,16,17) …”
mentioning
confidence: 99%
“…Figure 4 shows plots for the effect of temperature on the motion of 1,14) in aqueous dispersions of pure DPPC, melting point 41C, and in mixtures of DPPC and polar lipids from wheat roots which on their own show a transition at -6°C (19). Since the plots for the pure DPPC and the mixtures containing up to 50% DPPC appear to consist of two linear segments connected by a curve, the data were analyzed by two methods: (a) by fitting straight lines and determining the temperature at which there is a significant increase in the temperature coefficient of spin label motion (slope) as temperature decreases and (b) fitting the data to an equation developed by Klein (10) to define rate processes in membranes.…”
mentioning
confidence: 99%